Association of less common cystic fibrosis mutations with a mild phenotype. Issue 1 (January 1991) - Curtis, A; Nelson, R; Porteous, M; Burn, J; Bhattacharya, S S
Abstract : A majority of cystic fibrosis (CF) genes (70 to 75%) share a single mutation, but the remaining 25 to 30% of defects are accounted for by more than 20 different mutations. One of the less frequent mutations, G551D, has been identified in the CF genes of two sibs and one unrelated adult patient. The adult patient also has a second rare mutation, delta I507. All three subjects exhibit a less severe phenotype than that normally associated with CF. This supports a hypothesis that the common mutation (delta F508) is responsible for the severe form of the disorder, and the minority of patients with a milder form tend to have mutations at other sites in the CF gene.